Classification of E-Commerce Shipping Timeliness Using Supervised Learning Algorithm - Pratama, Novrian; Anrahvi, Rifka; Tambal, Ahmed; Singh, Aryanshi (Institute of Research and Publication Indonesia (IRPI)., 2025)
Developments in the e-commerce sector have increased rapidly since the onset of COVID-19, which has changed consumers' shopping habits. The growth in the number of e-commerce consumers affects the demand for long-distance delivery of goods. The problem of late delivery of goods is one of the challenges that is often experienced, and this can affect the level of customer satisfaction. This study aims to analyze whether the delivery of goods has been carried out according to schedule or has experienced delays. By using e-commerce shipping datasets obtained through the website, this research applies five supervised learning algorithms in the classification process, namely Decision Tree, Naïve Bayes Classifier, K-Nearest Neighbors (K-NN), Random Forest, and Support Vector Machine (SVM). The evaluation results show that dataset sharing using the K-Fold Cross Validation technique provides the best performance at K=8. Support Vector Machine showed the highest level of accuracy of 66.35%, followed by precision of 69.31% and recall of 66.35%. In contrast, the Naïve Bayes Classifier algorithm recorded the lowest performance with accuracy 64.22%, 97.73% precision, and 42.67% recall. These results show that the SVM algorithm is better at classifying the timeliness of delivery compared to the other four algorithms.